Synthesis and Characterization of Silicone-Based Surfactants as Anti-Foaming Agents - Kekevi, Burcu; Berber, Hale; Yildirim, Huseyin (SPRINGER HEIDELBERG, 2012)
Silicone-based amphiphilic surfactants were synthesized as anti-foaming agents through a polycondensation reaction between chlorine-terminated polysiloxane and polyethers. Poly(ethylene glycol) (PEG) and poly(propylene glycol) of different molecular weights were used. The structures of these tri-block co-polymers were characterized by FTIR, (1)H NMR and ESI-MS analysis. Surface tension, foam height and foam destruction properties of these co-polymers were determined. Spectroscopic analysis confirmed that bonding of polyether to polysiloxane was successful and two types of different tri-block co-polymers were obtained. The anti-foaming efficiency of these co-polymers tended to increase with an increase in the hydrophilic character of the co-polymer chains. The synthesized tri-block co-polymers, which can be used as anti-foaming agents in paper-coating applications of poly(vinyl acetate-co-butyl acrylate) latexes, showed low surface tension values, fast liquid drainage and efficient foam destruction. PEG 200-b-PDMS-b-PEG 200 was determined to be the most efficient anti-foaming agent among all co-polymers synthesized.
Keywords: Anti-foaming agent; Silicone surfactants; Polyethers; Tri-block co-polymers; Foaming properties; Ross-Miles test; WATER; SYSTEMS; POLYOXYETHYLENE; TENSION; Chemistry; Engineering